Early and Late Effects of rt-PA vs Placebo on Left Ventricular Function Measured by Nuclear Ventriculography - Mortelmans, L.; Scheys, I.; Brzostek, T.; Lesaffre, E.; De Roo, M.; Verstraete, M.; De Geest, H.; Van de Werf, F. (Nuklearmedizin - NuclearMedicine, 1993)
The aim of the study was the functional re-evaluation of 296 patients 12 to 18 months after a double-blind trial evaluating the effect of tissue plasminogen activator (rt-PA) versus placebo given within 5 h of onset of symptoms caused by an acute myocardial infarction. All patients underwent rest-stress radionuclide angiography (Egna). For each exercise level the global left ventricular ejection fraction (LVEF) was calculated together with an estimate of regional wall motion abnormalities (RWMA). A clear difference of the total workload and the peak workload was found between both therapeutic groups. Discriminant analysis evaluating four parameters (LVEF at peak exercise and at the endpoint and the workload at those levels) revealed a beneficial therapeutic effect. The RWM at rest showed only a difference in the apico-inferior region. There were less wall motion abnormalities in the treated group. Radionuclide analysis demonstrated a larger functional capacity and a better coordination of myocardial contractility during stress RNA one year after thrombolytic therapy. At rest, no major differences were found between the hospital stage and the follow-up in both therapeutic groups one year later.Ziel der Studie war die Bewertung der Ventrikelfunktion bei 296 Patienten 12 bis 18 Monate nach dem Doppelblindeinsatz von RTPA im Vergleich zu Plazebo, verabreicht innerhalb von 5 h nach Auftreten eines akuten Myokardinfarkts. Die Äquilibrium-Radionuklid-Ventrikulographie (ÄRNV) wurde in Ruhe sowie nach Belastung durchgeführt. Für jede Belastungsstufe wurden die globale linksventrikuläre Auswurffraktion (GAF) berechnet und Veränderungen der regionalen Wandbewegung (RWB) untersucht. Beide Gruppen unterschieden sich deutlich in bezug auf sowohl die Gesamt- als auch die Spitzenbelastung. Eine Diskriminanzanalyse für maximale GAF und GAF am Endpunkt zusammen mit der Belastung erbrachte in der RTPA-Gruppe eine bessere globale Ventrikelfunktion. Für RWB in Ruhe ergaben sich Differenzen für das apiko-inferiore Segment. In der RTPA-Gruppe waren weniger Wandbewegungsstörungen zu beobachten. Mittels der Belastungs-ÄRNV konnte gezeigt werden, daß ein Jahr nach der thrombolytischen Therapie eine größere Funktionsreserve und eine bessere myokardiale Kontraktilität im Vergleich zum Plazebo vorhanden war. Bei Untersuchungen in Ruhe ergaben sich keine Unterschiede zwischen der Postinfarktperiode und der Kontrolle nach einem Jahr.
Keywords: Radionuclide ventriculography; myocardial infarction; thrombolysis; ejection fraction